The Effect Of Accounting Knowledge And Business Scale On The Preparation Of SAK EMKM Financial Statements (Empirical Study of MSMEs in Kota Manna District of South Bengkulu Regency) - Andri Adriansyah; Ahmad Sumarlan; Nensi Yuniarti. Zs; Dinal Eka Pertiwi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
One of efforts to improve the performance and sustainability of MSMEs is to improve the understanding of MSME owners on an understanding of accounting. It can assist MSME actors in properly recording, so that business profits can be correctly identified and their management and accountability can be properly accounted. The purpose of this study is to obtain evidence about the effect of accounting knowledge and bussines scale on the preparation of SAK EMKM financial statements for MSMEs in kota Manna district of South Bengkulu Regency. This research technique was quantitative descriptive type. The data was collected by using the observation, questionnaires and documentation. The methods of data analysis used were the descriptive data analysis and multiple regression analysis with α 0.05. The results of this study indicate that partially the accounting knowledge has a positive and significant effect on the preparation of SAK EMKM financial statements, while the business scale does not have a significant effect on the preparation of SAK EMKM financial statements. There is simultaneously the effect of the accounting knowledge and the business scale on the preparation of SAK EMKM financial reports. Keywords: Knowledge of Accounting, Business Scale, SAK EMKM, Financial Statements